Congenital Anaplastic Rhabdomyosarcoma Presenting As Abdominal Wall Mass - KRISHNENDU MONDAL; RUPALI MANDAL (Iranian Society of Pathology, 2016)
Rhabdomyosarcoma encompasses a group of malignant myogenic neoplasms expressing a multitude of clinical and pathological diversities. It is the commonest soft tissue sarcoma of childhood but neonates are rarely affected. Embryonal subtype is the most frequent. Head-neck and genitourinary tracts are predominant sites, while trunk is considered among the unusual sites of rhabdomyosarcoma. Herein we report a case of anaplastic rhabdomyosarcoma in a newborn girl presenting, at the pediatric surgery outpatient department of North Bengal Medical College and Hospital on 2013 with a large tumour mass in the left flank region, arising from abdominal wall muscles.